Ekstrak Daun Kelor (Moringa oleifera Lamk.) sebagai Penurun Kadar Glukosa Darah Mencit Jantan (Mus musculus L.) Hiperglikemik - Susi Dewiyeti; Saleh Hidayat (Jurnal Penelitian Sains, 2015)
Diabetes mellitus is a disease that needs multidiscipline and long life treatment, so herbal alternative is wanted. Moringa oleifera Lamk. is one of multipurpose plant. Moringa leaves has substances that can be used as an anti-hyperglycemic. To reveal the substances contribute to antidiabetic effect of Moringa leave, an antidiabetic test was done mice (Mus muscullus L.) strain Swiss Webster. The main purpose of this research were: (1) to determine the effect of leaf extracts of Moringa to decrease blood glucose levels in mice strain Swiss Webster alloxan induced? This research method used experimental method in the laboratory a completely randomized design consisted of 6 treatments and 4 replications consist. The treatments consisted of the P0 = normal control (it is given aquadest and animal food), P1 = positive control (alloxan induced and aquadest) P2 = comparison (induced alloxan and glibenclamide), P3 = 10% mixture of moringa leaf extract, P4 = 20%, and P5 = 30% is given in a gevage given for 10 days. The mice are chosen randomly with the body weight 25-35 grams with the age of 2-3 months. The result of the reseach: 1) extracting of moringa leaves on various concentration (10%, 20% and 30%) were capable to decrease in blood glucose mice significantly 0.000 < α 0.05. 2) Mouse weight had correlation with blood glucose level of mice that showed R = 0.49. It’s means that, giving extract moringa leave (Moringa oleifera Lamk.) hadn’t effect toward blood glucose level of mice.